A Titanium and Tantalum Phosphate LiNaTiTa2P2O13 with An Open Framework hosting Li and Na Ions. Issue 62 (4th October 2021) - Zhou, Jingfang F.; Li, Rukang K.
Abstract: Herein, we report a detailed structural, electric, thermal and optical analysis of a titanium and tantalum phosphate LiNaTiTa2 P2 O13 . The title compound is comprised of typical ReO3 ‐type layers constituted by corner‐sharing TiO6 and TaO6 octahedra, bridged by PO4 tetrahedra, and the structure is closely related to monophosphate niobium bronzes. The existence of pentagonal tunnels, hosting the Li + and Na + ions, endows LiNaTiTa2 P2 O13 a moderate ion transportation behavior (4.67×10 −4  S/cm at 823 K). In addition, the successful substitution of Nb for Ta in LiNaTiTa2 P2 O13 results in the optical absorption red‐shift towards visible range with a narrowing band gap, which may provide a route of isomorphic replacement to band engineering for photo‐catalysis. Abstract : LiNaTiTa2 P2 O13 displays an open framework comprised of staggered [Ti1/3 Ta2/3 O3 ]∞ layers and PO4 tetrahedra with a herringbone‐like stacking pattern, similar to monophosphate niobium bronzes. The existence of pentagonal tunnels, hosting the Li + and Na + ions, endow LiNaTiTa2 P2 O13 a moderate ion transport capability (4.67×10 −4  S/cm at 823 K). In addition, the layers constituted by corner‐sharing TiO6 and TaO6 octahedra endow a possibility as being photo‐catalyst. The successful substitution of Nb for Ta results in the optical absorption red‐shifted towards visible range with a narrowing band gap comparable to that of TiO2 (3.2 eV).